Recent Publications (Quarterly Journal of Economics, 1963)
Recent Publications Get access The Quarterly Journal of Economics, Volume 77, Issue 2, May 1963, Pages 343–347, https://doi.org/10.1093/qje/77.2.343 Published: 01 May 1963